2004
DOI: 10.1038/sj.eye.6701749
|View full text |Cite
|
Sign up to set email alerts
|

Acute nonarteritic ischaemic optic neuropathy after phentermine

Abstract: Sir, Acute nonarteritic ischaemic optic neuropathy after phentermineAmphetamine derivatives used in weight reduction regimens are considered safe for use over a several week period. Ischaemic and/or haemorrhagic infarcts and necrotizing angiitis are common neurologic complications of amphetamine abuse. Ocular side effects of amphetamine abuse include mydriasis, decreased accommodation and convergence, visual hallucinations (blue tinge to objects), retinal vasoconstriction and vasculitis, retinal microaneurysms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“… 3 , 4 , 5 These reports concluded that phentermine's sympathetic properties can cause vasoconstriction and vasospasm leading to ischemia in different organ systems. Chan 6 reported a 35-year-old woman who developed an acute non-arteritic anterior ischemic optic neuropathy (NAION) after taking two prescribed dosages of phentermine. Consequently, he concluded that the patient's vision loss was due to vasoconstriction of the posterior ciliary arteries secondary to phentermine use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 , 4 , 5 These reports concluded that phentermine's sympathetic properties can cause vasoconstriction and vasospasm leading to ischemia in different organ systems. Chan 6 reported a 35-year-old woman who developed an acute non-arteritic anterior ischemic optic neuropathy (NAION) after taking two prescribed dosages of phentermine. Consequently, he concluded that the patient's vision loss was due to vasoconstriction of the posterior ciliary arteries secondary to phentermine use.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 While studies have shown that this drug is safe, several case reports have demonstrated phentermine being associated with adverse effects including stroke, myocardial infarction, and ischemic ocular diseases. 3 , 4 , 5 , 6 , 7 , 8 In addition, other amphetamine derivatives, especially ones that are abused like methamphetamine and cocaine, have been well documented to have harmful effects on the cardiovascular, neurologic, and psychologic systems. 9 In particular, ocular side effects of amphetamine abuse include mydriasis, decreased accommodation and convergence, visual hallucinations, retinal vasoconstriction and vasculitis, retinal microaneurysms and hemorrhage, and anterior ischemic optic neuropathy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphetamine isomers have been described to induce acute nonarteritic ischaemic optic neuropathy. 2 Ecstasy also activates the hypothalamic pituitary adrenal axis, which induces a significant rise in cortisol plasma concentrations and a depression in immune function. [3][4][5] In summary, we present here a patient with long-standing, unrecognized posterior scleritis.…”
Section: Commentmentioning
confidence: 99%